Descriptive study of burnout, compassion fatigue and compassion satisfaction in undergraduate nursing students at a tertiary education institution in KwaZulu-Natal - Christina T. Mathias; Dorien L. Wentzel (AOSIS, 2017)
Background: Studies have investigated burnout and compassion fatigue among nurses and effects in the nursing profession. However, there are limited investigations of burnout and compassion fatigue among undergraduate nursing students in South Africa, as nursing students may experience distressful situations during their nursing education course, which may have an impact during their training and in their profession as they graduate. Purpose: The purpose of this descriptive study was to describe compassion satisfaction, compassion fatigue and burnout among undergraduate nursing students at a tertiary nursing institution. Methods: A quantitative descriptive study was conducted to describe compassion satisfaction, compassion fatigue and burnout among undergraduate nursing students at a tertiary nursing institution in KwaZulu-Natal. Convenience sampling was used. Results: Sixty-seven undergraduate students (26 third-year and 41 fourth-year nursing students) took the self-test Professional Quality of Life Scale (ProQOL). The study results indicate that undergraduate students experienced average levels of compassion fatigue, burnout and compassion satisfaction. Conclusion: As shown in the study, some of the undergraduate students are experiencing compassion fatigue and burnout, associated with relieving suffering of others. Therefore, knowledge of compassion fatigue and burnout and the coping strategies should be part of nursing training.